Sodium alginate-egg white gel beads and preparation method thereof
By combining sodium alginate with egg white to form composite gel beads, the stability and release control problems of active substances caused by porosity of sodium alginate are solved, and the preparation of gel beads with high hardness and good physical destructive resistance is achieved to ensure that Effective protection and slow release of active substances.
Patent Information
- Application Number
- CN202410934318.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-12
AI Technical Summary
As a porous material, sodium alginate is easily penetrated by gastric acid, affecting the stability and release control of active substances embedded in its hydrogel beads.
Complex gel beads are formed by combining sodium alginate with egg white. The method includes dissolving sodium alginate in water, adding egg white, curing it in a solution containing Ca2+ and heating it to produce sodium alginate-egg white gel beads with high hardness and good resistance to physical destructiveness.
This method effectively improves the hardness and physical destructiveness of the gel beads, can better protect and control the release of active substances, and extends the structural stability of the gel beads.
Smart Images

Figure CN118725340B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gel bead preparation, and particularly relates to sodium alginate-egg white gel beads and a preparation method thereof. Background Art
[0002] Sodium alginate is a carbohydrate composed of 1,4-poly-β-D-mannuronic acid and α-guluronic acid. It is a biodegradable, low-cost and biocompatible biopolymer. Its molecule contains a large amount of -COO-. 2+ In the presence of cations, the Na on the α-guluronic acid unit + Ion exchange occurs with divalent cations, and the α-guluronic acid units stack to form a cross-linked network structure, thereby forming a hydrogel, so it is widely used in the preparation of hydrogel beads.
[0003] Sodium alginate is a porous material, so gastric acid can easily enter the interior of sodium alginate through the pores, affecting the active substances embedded in the sodium alginate hydrogel beads. Therefore, when using sodium alginate to embed active substances, it must be used in conjunction with other materials. In this case, the carboxylic acid free radicals on the sodium alginate molecular chain are combined with cations on other molecular chains to form a dense protective layer to protect and control the release of active substances.
[0004] Egg white is a kind of food that is necessary for daily life. Its main components are egg white, ovotransferrin and ovomucin. Its gel property plays a key role in food processing. Egg white in egg white can be deformed to form gel under heat-induced conditions. When heated, the α-helix and β-folded structure in the egg white molecule will unfold, and the free sulfhydryl groups and disulfide bonds in the structure will also be exposed. They are cross-linked through the interaction force between molecules, thereby enhancing the stability of the egg white and making the egg white have better gelling properties.
[0005] Polysaccharides and proteins are widely used in the production of food gels, either alone or in combination. Compared with single systems, mixed systems of polysaccharides and proteins can more effectively regulate gel texture. Even a simple mixture of protein and polysaccharide can produce a gel structure. Polysaccharides and proteins belong to different classes of macromolecules and show great differences in chemical structure, physical properties and functions. Therefore, in the mixture of polysaccharides and proteins, a wider range of phase behaviors can be generated. These phase behaviors may be due to long-chain or short-chain interactions between polysaccharides and proteins, or due to different affinities between polymers and solvents. Therefore, polysaccharide-protein complexes increase the diversity of gel structures. On the other hand, the combination of polysaccharides with proteins can prepare mixed gels with a variety of structures and higher nutritional value.
[0006] How to select appropriate polysaccharides and proteins for combination, realize the complementary advantages of polysaccharides and proteins, and prepare high-performance polysaccharide-protein composite gel beads is a topic to be studied in this field. Summary of the invention
[0007] The purpose of the present invention is to provide a sodium alginate-egg white gel bead and a preparation method thereof. By selecting sodium alginate and egg white as raw materials and following simple preparation steps, composite gel beads with high hardness and good resistance to physical damage are prepared, and the gel beads can well protect the delivery components as a carrier.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention is to provide a method for preparing sodium alginate-egg white gel beads, comprising the following steps: dissolving sodium alginate in water, adding egg white, mixing evenly, and then adding to a solution containing Ca 2+ The sodium alginate-egg white gel beads are prepared by curing in a solution and heating after curing.
[0010] Preferably, the usage ratio of the sodium alginate, the water and the egg white is 1.8 g:75 mL:125 mL.
[0011] Preferably, the Ca-containing 2+ The solution is a calcium lactate solution.
[0012] More preferably, the concentration of the calcium lactate solution is 4.15 g / 100 mL; the curing temperature is 34.5° C., and the curing time is 28 min.
[0013] Preferably, the heating temperature is 80° C. and the heating time is 10 min.
[0014] The second technical solution of the present invention is to provide sodium alginate-egg white gel beads prepared according to the preparation method of the sodium alginate-egg white gel beads.
[0015] The beneficial technical effects of the present invention are as follows:
[0016] The invention combines the advantages of sodium alginate and egg white, and prepares composite gel beads with high hardness and good resistance to physical damage by combining the advantages and avoiding the disadvantages.
[0017] Compared with sodium alginate gel beads, the sodium alginate-egg white gel beads provided by the present invention can better maintain their structural state when physically damaged, thereby achieving a better protection effect on the delivered components.
[0018] The preparation method provided by the invention is simple, is conducive to large-scale promotion and application, and has high economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a graph showing the effect of calcium lactate concentration on the hardness of sodium alginate-egg white gel beads in Example 1.
[0020] Figure 2 This is a graph showing the effect of curing time on the hardness of sodium alginate-egg white gel beads in Example 1.
[0021] Figure 3 This is a graph showing the effect of curing temperature on the hardness of sodium alginate-egg white gel beads in Example 1.
[0022] Figure 4 It is the response surface and contour map in Example 2, wherein (a) is the contour map of the interaction between calcium lactate concentration and curing time, (b) is the response surface of the interaction between calcium lactate concentration and curing time, (c) is the contour map of the interaction between calcium lactate concentration and curing temperature, (d) is the response surface of the interaction between calcium lactate concentration and curing temperature, (e) is the contour map of the interaction between curing time and curing temperature, and (f) is the response surface of the interaction between curing time and curing temperature.
[0023] Figure 5 These are the texture analysis results of the sodium alginate-egg white gel beads and the sodium alginate gel beads in Example 3.
[0024] Figure 6 This is a SEM image of the surface of the sodium alginate xerogel beads in Example 3 magnified 500 times.
[0025] Figure 7 This is a SEM image of the cross section of the sodium alginate xerogel beads in Example 3 magnified 500 times.
[0026] Figure 8 This is a SEM image of the surface of the sodium alginate-egg white xerogel beads in Example 3, magnified 500 times.
[0027] Fig. 9 This is a SEM image of the surface of the sodium alginate-egg white xerogel beads in Example 3, magnified 50,000 times.
[0028] Fig.10 This is a SEM image of the cross section of the sodium alginate-egg white xerogel beads in Example 3, magnified 500 times.
[0029] Fig.11 This is a SEM image of the cross section of the sodium alginate-egg white xerogel beads in Example 3, magnified 2000 times.
[0030] Fig.12 1 is the XRD diagram of sodium alginate-egg white xerogel beads and sodium alginate xerogel beads in Example 3.
[0031] Fig.13This is the infrared spectra of the sodium alginate-egg white xerogel beads, sodium alginate and egg white in Example 3. DETAILED DESCRIPTION
[0032] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0033] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the invention.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] The room temperature in the embodiment of the present invention refers to a temperature of 25±5° C.; the egg white in the embodiment of the present invention comes from fresh eggs purchased from a supermarket; the sodium alginate and calcium lactate used in the embodiment of the present invention are both food grade and purchased from Qingdao Mingyue Seaweed Group Co., Ltd.
[0037] The percentage concentration of calcium lactate in the examples refers to 1g·100mL -1 .
[0038] Example 1
[0039] Single factor experiment on process parameters in the preparation of sodium alginate-egg white gel beads
[0040] Weigh 1.8 mL of sodium alginate and add it to 75 mL of ultrapure water. Heat and stir at 50°C until the sodium alginate is completely dissolved. After the sodium alginate is completely dissolved, cool it down, then slowly add 125 mL of egg white and mix evenly to obtain a sodium alginate-egg white mixed solution. Use a peristaltic pump to drop the sodium alginate-egg white mixed solution into the prepared calcium lactate solution of different concentrations and temperatures, let it stand and solidify for a certain period of time, filter out the gel beads after solidification, wash them with ultrapure water 1-2 times, and seal them in pure water for storage. Heat the prepared gel beads in an 80°C water bath for 10 minutes to obtain sodium alginate-egg white gel beads.
[0041] Taking the hardness of sodium alginate-egg white gel beads as an index, in the single factor experiment of calcium lactate concentration (1%, 2%, 3%, 4%, 5%) (m / v), the experimental conditions were controlled as a curing time of 30 min and a curing temperature of room temperature; in the single factor experiment of curing time (15, 30, 45, 60 min), the experimental conditions were controlled as a calcium lactate concentration of 5% and a curing temperature of room temperature; in the single factor experiment of curing temperature (30, 35, 40, 45, 50, 55, 60°C), the experimental conditions were controlled as a calcium lactate concentration of 5% and a curing time of 30 min.
[0042] The hardness test method of sodium alginate-egg white gel beads is as follows: the hardness of wet gel beads is measured by physical property analyzer. This test uses TA / 0.5 gel probe, and the test conditions are set in TPA test mode: pre-test speed 1mm / s, test speed 1mm / s, post-test speed 1mm / s, compression degree 30%, trigger force 4gf, time 5s. Select a gel bead with a complete and round appearance from the sample, place it in the center of the test bench, and test the height and hardness index of the gel bead sample. Each group of tests is repeated 10 times.
[0043] Figure 1 The figure shows the effect of calcium lactate concentration on the hardness of sodium alginate-egg white gel beads. Figure 1 It can be seen that the effect of calcium lactate solution concentration on the wet ball hardness of gel beads first increases and then decreases. This may be because when the concentration of calcium lactate solution is low, the Ca in the system 2+ The content is low, so when cross-linking occurs, only part of the sodium alginate participates, so the strength of the formed gel structure is low; when the sodium alginate solution is dropped into the high concentration of calcium lactate, a dense gel structure will be formed instantly, which affects the continued penetration of calcium lactate, causing the mechanical strength of the gel beads to decrease, and thus the hardness is also reduced. The final analysis determined that the optimal concentration of calcium lactate solution is 4%.
[0044] Figure 2 The figure shows the effect of curing time on the hardness of sodium alginate-egg white gel beads. Figure 2It can be seen that the speed of cross-linking of sodium alginate and calcium lactate to form gel is very fast. The results of this experiment can also prove this point. After curing for a period of time, the effect of curing time on the hardness of the gel beads no longer changes significantly. Considering the economic benefits, the optimal curing time is determined to be 30 minutes.
[0045] Figure 3 The figure shows the effect of curing temperature on the hardness of sodium alginate-egg white gel beads. Figure 3 It can be seen that as the temperature increases, the chain segments of sodium alginate molecules are entangled to a certain extent, which is conducive to combining with calcium ions to form a network structure, and the gel properties become better. However, as the temperature continues to rise, the α-guluronic acid and 1,4-poly-β-D mannuronic acid segments in the sodium alginate molecules are easy to separate and are not easy to form a network structure with calcium ions, and the gel properties become worse; at the same time, when the temperature rises to 55-60°C, egg white protein begins to denature, which hinders the calcium ions from forming a network structure with the internal sodium alginate, causing the hardness of the gel beads to decrease.
[0046] Example 2
[0047] Response surface experiment of process parameters in the preparation of sodium alginate-egg white gel beads
[0048] According to the single factor test analysis, the response surface test was designed. First, three factors with significant effects on the hardness of egg white-sodium alginate gel beads were selected: calcium lactate solution concentration, curing time and curing temperature. These three factors with significant effects were used as independent variables, and the hardness of gel beads was used as the response value. The response surface combination was designed by Design-Expert 13 software to optimize the preparation process of egg white-sodium alginate gel beads. The response surface factors and level design are shown in Table 1.
[0049] Table 1 Factors and levels of response surface experiment
[0050]
[0051]
[0052] Response surface experiment results:
[0053] A complete regression analysis was performed on each set of data using Design-Expert 13 software, and the regression equation for the three factors and the hardness of the gel beads was obtained: Y / % = 17.12 + 0.5231A - 0.1471B - 0.3095C - 0.3838AB + 0.3005AC + 0.1160BC - 1.80A 2 -0.8888B 2 -1.45C 2 The results of the response surface experiment are shown in Table 2.
[0054] The regression model was subjected to variance analysis, and the regression equation R 2 =0.9821, the regression model is significant (P < 0.0001), the lack of fit term is 0.6046, which is not significant, and the pure error value is relatively small, which proves that this model can be used to analyze and predict the hardness of sodium alginate-egg white gel beads, and the experimental error is small. The P value of the concentration of calcium lactate solution in the model is less than 0.01, indicating that the concentration of calcium lactate solution has the most significant effect on the hardness of sodium alginate-egg white gel beads. The influence of each factor in the first term on the hemicellulose extraction rate in pineapple peel residue is ranked in the following order: A (concentration of calcium lactate solution) > C (curing temperature) > B (curing time). The results of variance analysis are shown in Table 3.
[0055] Table 2 Response surface experimental design and results
[0056]
[0057]
[0058] Table 3 Analysis of variance of response surface model
[0059]
[0060] Note: ** indicates extremely significant difference (P < 0.01); * indicates significant difference (P < 0.05)
[0061] Response surface analysis results
[0062] The response surface and contour map obtained according to the regression equation are shown in Figure 4 As shown, (a) is the contour map of the interaction between calcium lactate concentration and curing time, (b) is the response surface of the interaction between calcium lactate concentration and curing time, (c) is the contour map of the interaction between calcium lactate concentration and curing temperature, (d) is the response surface of the interaction between calcium lactate concentration and curing temperature, (e) is the contour map of the interaction between curing time and curing temperature, and (f) is the response surface of the interaction between curing time and curing temperature. The shape and sparseness of the contour lines show the influence of the interaction between the two factors on the hardness of sodium alginate-egg white gel beads. If the contour lines are elliptical, the influence is strong, and if the contour lines are circular, the influence is weak.
[0063] Depend on Figure 4 It can be seen that the interaction between A (concentration of calcium lactate solution) and B (curing time) is more significant, and the contour curve is steeper, indicating that the interaction between these two groups of factors is the most significant, and the effect on the hardness of sodium alginate-egg white gel beads is the most significant; followed by A (concentration of calcium lactate solution) and C (curing temperature); while the interaction between B (curing time) and C (curing temperature) is less effective than AC and BC. The results of variance and response surface test analysis are consistent.
[0064] After analysis and optimization by Design-Expert13, the optimal process conditions for preparing sodium alginate-egg white gel beads are: calcium lactate solution concentration of 4.15042% (w / v), curing time of 28.1658min, and curing temperature of 34.5165℃. Under this condition, the hardness of sodium alginate-egg white gel beads is 17.1869gf. Considering the experimental conditions and the needs of actual production, the optimal extraction conditions are adjusted to: calcium lactate solution concentration of 4.15% (w / v), curing time of 28min, and curing temperature of 34.5℃, and three parallel tests are carried out. The hardness of sodium alginate-egg white gel beads is 16.469gf, which is 0.718gf different from the theoretical value, proving that this model is feasible for optimizing the preparation process of sodium alginate-egg white gel beads.
[0065] Example 3
[0066] Preparation of sodium alginate-egg white gel beads
[0067] Sodium alginate-egg white gel beads were prepared using the optimal process parameters optimized in Example 2, and sodium alginate gel beads prepared using 1 g / 100 mL of sodium alginate solution at a calcium lactate concentration of 4.15%, a temperature of 34.5° C., and a curing time of 28 min were used as a control.
[0068] The texture analysis of the prepared sodium alginate-egg white gel beads and sodium alginate gel beads was carried out. Figure 5 As shown, Figure 5 It is shown that after the addition of egg white, the hardness and elasticity of the gel beads are reduced. The reduction in the hardness of the gel beads may be due to the interaction between egg white and sodium alginate, which reduces the groups of sodium alginate that can cross-link with calcium ions, making the hardness of the composite gel beads not as good as that of the sodium alginate gel beads. Although the hardness is lower than that of sodium alginate gel beads, it does not affect the delivery as a functional ingredient. This is because even with a lower hardness, the gel beads can still maintain sufficient structure to wrap and protect the functional ingredients contained therein, ensuring slow release during digestion. Although the elasticity is lower than that of sodium alginate gel beads, it does not affect the taste when eaten, and is more suitable for addition to yogurt or pudding as a carrier of functional ingredients.
[0069] The apparent structure and internal structure of sodium alginate-egg white gel beads and dried gel beads of sodium alginate gel beads were observed using a scanning electron microscope. The dried gel bead samples were fixed on an adhesive plate and gold-sprayed, and the sample structure was magnified and observed at a voltage of 5.0 kV. Figure 6 This is a SEM image of the surface of sodium alginate xerogel beads magnified 500 times. Figure 7 This is a SEM image of the cross section of sodium alginate xerogel beads magnified 500 times. Figure 8 This is a SEM image of the surface of sodium alginate-egg white xerogel beads magnified 500 times. Fig. 9This is a SEM image of the surface of sodium alginate-egg white xerogel beads magnified 50,000 times. Fig.10 This is a SEM image of the cross section of sodium alginate-egg white xerogel beads magnified 500 times. Fig.11 This is a SEM image of the cross section of sodium alginate-egg white xerogel beads magnified 2000 times.
[0070] Figure 7 to Figure 11 It shows that compared with the surface state of sodium alginate dry gel beads, the surface of sodium alginate-egg white dry gel beads is smoother, and the surface shrinkage caused by water loss is lighter, which reduces the loss of delivery components due to shrinkage and denaturation of the gel beads surface to a certain extent. Comparing the cross-sectional structures of the two substances, it can be observed that the cross-sectional fragmentation of sodium alginate dry gel beads is more serious, and sodium alginate-egg white dry gel beads can better maintain their structural state when physically damaged, thereby providing better protection for the delivery components.
[0071] The dried gel beads samples of sodium alginate-egg white gel beads and sodium alginate gel beads were analyzed by X-ray diffractometer. The scanning speed was 4° / min and the scanning angle (2θ) was within the range of 5-80°.
[0072] The XRD patterns of sodium alginate-egg white xerogel beads and sodium alginate xerogel beads are shown in Fig.12 .from Fig.12 It can be seen that the sodium alginate dry gel beads have only one broad peak at 20.98°, while the sodium alginate-egg white dry gel beads have two diffraction peaks, and the peak intensity of the sodium alginate-egg white dry gel beads is significantly higher than that of the sodium alginate dry gel beads. The first diffraction peak of the sodium alginate-egg white dry gel beads is located at 9.16°, showing that the sodium alginate-egg white dry gel beads have an ordered structure and ordered structure fragments; the second diffraction peak moves to a larger scattering angle of 19.11°, which is due to the interaction between egg white protein and sodium alginate. Compared with the sodium alginate dry gel beads, the XRD spectrum of the sodium alginate-egg white dry gel beads shows a more obvious large package peak state, and the gel beads tend to be more crystalline structure, which belongs to the amorphous state of OVA protein, which shows that the sodium alginate-egg white composite structure is more stable and can better encapsulate and deliver components.
[0073] The dried gel beads of sodium alginate-egg white gel beads and the dried products of sodium alginate and egg white were analyzed by infrared spectrometer to study their crystal structure. The samples were ground and spread flat in the sample tank, and the scanning range was 4000-400cm at room temperature. -1 , scanning rate is 4-40cm -1 .
[0074] The infrared spectra of sodium alginate-egg white xerogel beads, sodium alginate and egg white are shown in Fig.13 . Fig.13It shows that sodium alginate, egg white, and gel beads are at 3280-3270cm -1 The characteristic peaks of hydrophilic -OH stretching vibration appeared at 2940-2920cm -1 The characteristic peak is produced by the asymmetric stretching vibration of the hydrophobic -CH2-. Sodium alginate has a peak at 1590cm -1 、1410cm -1 、1030cm -1 The characteristic peaks at 1630cm represent the asymmetric stretching vibration of -COO-, the symmetric stretching vibration of -COO-, and the stretching vibration of -CO. -1 、1510cm -1 The characteristic peaks represent the stretching vibration of -C=O in the amide I band, the bending vibration of -NH in the amide II band, and the stretching vibration of -CN. The sodium alginate-egg white gel beads have a peak at 1630 cm -1 The -C=O peak at 1510cm indicates that the gel beads contain egg white; the addition of sodium alginate makes the egg white 1510cm -1 The characteristic peak at 1520cm -1 The shift occurred, indicating that the amino acid residues in the egg white had an electrostatic interaction with the carboxyl groups of the sodium alginate; the gel beads were at 1400 cm -1 The characteristic peak at is the absorption peak produced by the symmetrical carboxylate stretching vibration, which indicates that the interaction between sodium alginate and egg white increases the peak value of the characteristic peak of sodium alginate.
[0075] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing sodium alginate-egg white gel beads, characterized in that: The following steps are involved: Dissolving sodium alginate in water, adding egg white, mixing evenly, adding to a solution containing calcium lactate for solidification, and heating after solidification to obtain the sodium alginate-egg white gel beads; The dosage ratio of the sodium alginate, the water and the egg white is 1.8 g:75 mL:125 mL; The concentration of the calcium lactate solution is 4.15 g / 100 mL; the curing temperature is 34.5° C. and the curing time is 28 min; The heating temperature is 80° C. and the heating time is 10 min.
2. Sodium alginate-egg white gel beads prepared according to the preparation method of sodium alginate-egg white gel beads according to claim 1.